Analisis Kesulitan Siswa SD Dalam Mengidentifikasi Ide Pokok Paragraf Di SDN Sempu 2 - Dzambiyah, Asfiyatu; Rakhman, Patra Aghtiar; Rokmanah, Siti (Universitas Negeri Surabaya, 2024)
The purpose of this study was to describe the difficulty of students in determining the main idea in a paragraph. The research approach used is a qualitative approach with research methods in the form of descriptive research methods. Data sources taken in the form of interviews, observations, journals, articles, books, and other scientific works that are relevant and in accordance with the object of research study. Data collection techniques used, namely observation, interviews and documentation. Data analysis uses analysis from Miles and Huberman. The results showed that there were 2 causes of students' difficulties in determining the main idea of a paragraph, namely internal and external factors, internal factors include, 1) students do not understand the main idea of a paragraph; 2) students have not been able to distinguish between which are the main sentences and explanatory sentences; 3) students do not like the main idea material; 4) lack of interest in reading in students. While external factors include, 1) the lack of teacher methods and strategies in providing main idea material so that students dislike main idea material; 2) the use of local languages that become everyday language.